The Effect of Transformational Leadership Style on Employee Performance Through Organizational Culture as an Interverning Variable - Chaerudin, Abdul Rauf; Okaviani, Lulu Laujiah (LPPM Universitas Bina Bangsa, 2023)
The existence of human resources in a company has a very important role. One of the important factors related to human resources that affect the progress and development of a company is employee performance. Factors that affect performance include transformational leadership style and organizational culture. This study aims to determine the effect of transformational leadership style on employee performance, the effect of transformational leadership style on organizational culture, the influence of organizational culture on employee performance, and the influence of transformational leadership style on employee performance through organizational culture as an interverning variable at PT. XYZ. This research uses correlational quantitative method. The sampling technique used is a saturated sample with a population of 37 respondents, data obtained from primary data by distributing questionnaires. This research is processed using smartPLS version 3.3.9. The results of the calculation of transformational leadership style (X) on employee performance (Y) have a path coefficient of -0.217 with a t-statistic value of 1.939 < 1.96 and P-values 0.053> 0.05. The results of the calculation of transformational leadership style (X) on organizational culture (Z) have a path coefficient of 0.865 with a t-statistic value of 16.418> 1.96 and P-values 0.000 <0.05. The results of the calculation of organizational culture (Z) on employee performance (Y) have a path coefficient of 1.120 with a t-statistic value of 12,404> 1.96 and P-values of 0.000 <0.05. The results of the calculation of the indirect effect of transformational leadership style (X) through organizational culture (Z) on employee performance (Y) has a path coefficient of 0.969 with a t-statistic value of 9.285> 1.96 and p-values 0.000 < 0.05. In this study it can be concluded that transformational leadership style has no significant effect on employee performance, transformational leadership style has a significant influence on organizational culture, organizational culture has a significant effect on employee performance, and transformational leadership style has a significant effect on employee performance through organizational culture as interverning variable